FUR KNITWEAR KNITTED FROM SPUN COTTON NITRO YARN ANALYSIS OF PHYSICAL MECHANICAL INDICATORS OF TISSUES (Conferencea, 2023)
In this work, research was conducted in order to determine the high-quality options based on the analysis of rubber and interlock fabrics woven in different options of cotton and spun cotton-nitron yarns.